Eight-Week Low-Intensity Squat Training at Slow Speed Simultaneously Improves Knee and Hip Flexion and Extension Strength - Akagi, Ryota; Sato, Shinya; Hirata, Naoya; Imaizumi, Naoto; Tanimoto, Hiroki; Ando, Ryosuke; Ema, Ryoichi; Hirata, Kosuke (Frontiers in Physiology, 2020)
Considering that the squat exercise requires flexion and extension of the knee and hip joints, a resistance training program based on squat exercises should efficiently increase the flexion and extension strength of both the knee and hip. To our knowledge, however, no study has simultaneously investigated the effects of squat training on both flexion and extension strength in both the knee and hip. Low-intensity squat exercises at slow speeds can be expected to effectively and safely improve knee and hip flexion and extension strength in a wide range of individuals. This study aimed to clarify whether knee and hip flexion and extension strength improved after an 8-week low-intensity squat training program at slow speed. Twenty-four untrained young men were randomly assigned to a training or control group. Participants in the training group performed 40% one-repetition maximum parallel squats at slow speed (4 s for concentric/eccentric actions), 3 days per week for 8 weeks. Before and after the intervention, isometric peak torque of the knee and hip flexors and extensors during maximal voluntary contraction (MVC) was determined. For the knee flexors and extensors, muscle volume was also measured. There were significant training-induced increases in peak torque (P < 0.05). The training effects on knee and hip extension torque (effect size = 0.36–0.38) were higher than those on knee and hip flexion torque (effect size = 0.09–0.13). The squat training used here increased both knee and hip flexion and extension strength, but the training effects on the flexion strength were less than those on the extension strength. Regarding the knee extensors, a significant training-related increase in muscle volume was found (P < 0.05) without neuromuscular adaptations. In addition, there were significant correlations between the training-induced increases in muscle volume and peak torque of KE. These results suggest that muscle hypertrophy may be responsible for increased muscle strength of the knee extensors after an 8-week low-intensity squat training program at slow speed.